2010
DOI: 10.1111/j.1440-1746.2010.06480.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic significance of gastric‐specific annexin A10 in diffuse‐ and intestinal‐type gastric carcinoma

Abstract: The ANXA10 protein expression is a novel marker of gastric differentiation, and is differentially expressed in IGC and DGC, with opposite prognostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Aberrant ANXA10 expression has been reported to be closely associated with adenocarcinomas of the gastric and pancreatobiliary system [17, 24] as well as colorectal carcinoma (CRC) [16, 2526]. The ANXA10 expression was highly related to gastric phenotype in the serrated pathway to colorectal carcinoma [16] and associated with poor prognosis in CRCs [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant ANXA10 expression has been reported to be closely associated with adenocarcinomas of the gastric and pancreatobiliary system [17, 24] as well as colorectal carcinoma (CRC) [16, 2526]. The ANXA10 expression was highly related to gastric phenotype in the serrated pathway to colorectal carcinoma [16] and associated with poor prognosis in CRCs [25].…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface ANXA2 expression was shown to be strongly upregulated during the progression from low-grade PanIN lesions to pancreatic adenocarcinoma [15]. Increased expression of ANXA10 was closely related to a gastric phenotype in serrated pathway to colorectal carcinoma [16] while the downregulation of ANXA10 was correlated with tumor progression in intestinal-type gastric carcinoma [17]. Compared to the other 12 members in human ANXA family, ANXA10 has distinct features including an unusual single codon deletion and loss of two main type II calcium-binding sites [9, 18], which could result in different functional consequences.…”
Section: Introductionmentioning
confidence: 99%
“…26 MUC6 has a cytoprotective role in forming a mucous barrier against hostile gastric acid. 27 As ANXA10 was characterized to have a role in gastric gland development and maintenance, 14 it was not surprised that ANXA10 expression was highly associated with MUC5AC and MUC6 positivity. Yao et al 28 first described gastric differentiation in serrated adenoma in 1999.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have shown that ANXA10 is a protein specifically expressed in the gastric mucosa, the Brunner gland of the duodenum and the urothelium. 14,15 The upregulation of ANXA10 in sessile serrated adenoma may indicate an aberrant gastric phenotype in colonic serrated neoplasia; as evidenced by the high expression of gastric foveolar (MUC5AC) and pyloric mucin (MUC6) in sessile serrated adenoma. 16,17 Colorectal cancers exhibiting molecular features related to serrated neoplasia pathways are closely associated with MUC5AC and MUC6 expression, 18 implying that gastric programming participates in the carcinogenesis of a subset of colorectal cancers.…”
mentioning
confidence: 99%
“…Annexin A10 is a nuclear annexin specifically expressed in foetal and adult gastric mucosa (Lu et al, 2011). It is down-regulated in gastric carcinoma .…”
Section: Tissue Distribution and Intracellular Localization Of Annexinsmentioning
confidence: 99%